TEMPORAL REGULATION AND EMERGENCY DECISION-MAKING SKILLS FOR FUTURE PILOTS - Adamanov, Rustem; Mezhenko, Oleksandr (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The article examines the critical role of time regulation and decision-making skills in emergencies on the professional performance of future pilots. The purpose of the research is a theoretical and empirical study of the importance of the above-mentioned skills and the means of their development in production activities. The following research methods have been used: literature review, case studies, simulation studies, content analysis, historical analysis, statistical analysis, methods of comparative analysis, methods of systematization and generalization, as well as the method of desk research in the form of secondary information analysis by topic (monitoring of Internet resources and professional publications). The decision-making process is considered from the standpoint of a cognitive approach, its key psychological components have been analyzed, such as problem recognition, information gathering, perception of time limits, evaluation of action options, and selection of a general strategy. Effective time management by a pilot has been reviewed as a proactive method of preventing emergency situations in aviation, the ability to respond to emergencies in a fast and coordinated manner, a capability to see resources and quickly make adequate decisions to minimize losses in unexpected professional conditions. In the course of the study, it has been proven that effective time regulation and dynamics of decision-making in emergencies are important components of aviation safety. The ability to manage time, make quick decisions and prioritize tasks is critical in the high-stress and time-sensitive aviation industry. Theoretical training, along with simulator training, is essential for the development of these skills. The analyzed case studies illustrate the impact of these skills on the safety component of the activity. The study highlights the importance of training, regulatory oversight and adapting to new technologies and best practices, the need for continuous learning and development, ensuring pilots can make effective decisions under pressure and maintain aviation safety